PENGARUH PERSEPSI HARGA DAN LOKASI USAHA TERHADAP MINAT BELI KONSUMEN PADA PRODUK BUKET DI KECAMATAN SEBERANG ULU II KOTA PALEMBANG - Ayu Susanti; Rismansyah Rismansyah; Erfan Robyardi (Universitas Nusa Cendana, 2022)
This study aims to determine the effect of Price Perception and Business Location on Consumer Buying Interest in bouquet products in Seberang Ulu II District, Palembang City. The research method used in this study is a quantitative method with a sample of 97 respondents. The data analysis technique is Multiple Linear Regression Analysis, Correlation Coefficient Analysis and Coefficient of Determination Analysis using SPSS statistical software version 21.The results of the analysis show that: 1) Price Perception has a significant effect on Consumer Buying Interest in bouquet products in Seberang Ulu II District, Palembang City; 2) Business Location has a significant effect on Consumer Buying Interest in bouquet products in Seberang Ulu II District, Palembang City; 3) Price Perception and Business Location have a significant effect simultaneously on Consumer Buying Interest in bouquet products in Seberang Ulu II District, Palembang City. Based on Adjusted R2, it shows that the contribution given by the Price Perception and Business Location to Consumer Buying Interest is 57.9% and the remaining 42.1% is influenced by other factors that not included in this study. Further researchers should add other variables that can increase consumer buying interest such as Promotion and Product Quality. Keywords: Price Perception, Business Location, Consumer Buying Interest